2010
DOI: 10.1080/00986440903287775
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Kelvin-Helmholtz Instability of Two Superposed Dielectric Finite Fluids in Porous Medium Under Vertical Electric Fields

Abstract: A weakly nonlinear theory of wave propagation in two superposed dielectric fluids streaming through porous media in the presence of vertical electric field and in the absence of surface charges at their interface is investigated in three dimensions. The method of multiple scales is used to obtain a dispersion relation for the linear problem and a Ginzburg-Landau equation with complex coefficients for the nonlinear problem, describing the behavior of the system. The stability of the system is discussed both ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…They found that the electric field plays a dual role in the stability criterion in the sense that it stabilized perturbations having relatively small wavenumbers if the dielectric constant of the upper fluid is smaller than that of the lower fluid and vice versa. For recent developments of this topic, see the investigations of El-Sayed and co-workers [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the electric field plays a dual role in the stability criterion in the sense that it stabilized perturbations having relatively small wavenumbers if the dielectric constant of the upper fluid is smaller than that of the lower fluid and vice versa. For recent developments of this topic, see the investigations of El-Sayed and co-workers [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical scheme for integrating Equations ( 7) and ( 8) is based on the pseudo-spectral methods; it means that the functions ψ and η are approximated by the finite Fourier series. Consequently, the boundary conditions for Equations (7) and (8) are periodic in space with the period 2 . The total amount of the Fourier harmonics used in calculation presented was N = 2 15 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For the numerical integration in time, we use the explicit fourth-order Runge-Kutta method with the step dt = 10 -6 . The initial conditions for (7) and (8) are taken in the form:…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For recent surveys regarding the developments of linear and nonlinear electromagnetic flows in porous media, see refs. [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%